Admissibility of covert surveillance evidence: a prolegomenon - Md. Abdul Jalil,; Abu Hena Mostofa Kamal, (Penerbit UKM, 2014)
This article presents the epistemology of a new but mostly neglected subject ‘admissibility of surveillance evidence.’ It addresses the complex issues around‘the proper limits of covert surveillance’ and ‘whether evidence obtained by the public authority in breach of statutory provision should be ruled inadmissible.’ Further, it analyses issues that have a profound relationship with ‘individual’s right of privacy’ and ‘public authority’s duties of conducting surveillance.’ In this research much emphasis is placed on case laws as persuasive precedents as there are no adequate statutory laws in some countries like Bangladesh and Malaysia which deal with this subject. It is hoped that the results of this research would attract the attention of policy-makers of some interested countries. It is also hoped that reasonable ethical and legal safeguards should be implemented to protect the rights of the people from future abuse.